1998
DOI: 10.1002/abio.370180304
|View full text |Cite
|
Sign up to set email alerts
|

Performance of airlift bioreactors in the cultivation of some antibiotic producing microorganisms

Abstract: The specific aspects of airlift reactors emphasizing their function relevance to particular application as bioreactors are presentedThe two main groups of airlift reactors -external-loop and concentric-tube reactors -were investigated on a pilot-plant scale with regard to their performance during the cultivation of unicellular and filamentous microorganisms which produce Baciwcin, Cephalosporin C and Nystatin. Some results were compared to those obtained in conventional stirred tank bioreactors. The comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Gravilescu and Roman (1998) showed that airlift reactors consistently had higher energy efficiencies of between 30% and 40% in a number of antibiotic fermentations, when compared with stirred tank reactors. This reflects a general trend of airlift reactors being more energy efficient than stirred tanks (Chisti, 1989).…”
Section: Power Consumptionmentioning
confidence: 99%
“…Gravilescu and Roman (1998) showed that airlift reactors consistently had higher energy efficiencies of between 30% and 40% in a number of antibiotic fermentations, when compared with stirred tank reactors. This reflects a general trend of airlift reactors being more energy efficient than stirred tanks (Chisti, 1989).…”
Section: Power Consumptionmentioning
confidence: 99%
“…For aerobic cultures, air injection, besides being responsible for providing oxygen to the cells, decreases the density of the gasliquid dispersion inside the inner tube, thus promoting recirculation and mixing of the reaction medium in the bioreactor. This mixing behavior implies lower power consumption for this reactor type, as reported by KrackeHelmet et al [2] and Gavrilescu and Roman [3]. However, generally speaking, the absence of mechanical agitation by impellers in the airlift setup results in a lower oxygen transfer rate.…”
Section: Introductionmentioning
confidence: 64%
“…The airlift reactor was first patented for use as a bioreactor by Lefrancois in 1955 (Gavrilescu and Roman, 2004). Due to the fluid dynamic characteristics, it continues to gain popularity for its success in the production of microorganisms (Siegel et al, 1988;Kim et al, 1997).…”
Section: Types Of Bioreactorsmentioning
confidence: 99%